The Role of Public-Private Partnership in the Sustainable Development of the Rural Tourist Destinations - Gabriela Pascariu; Dragan Gabriela (European Regional Science Association (ERSA), 2006)
The perspectives of the international tourism development justify the interest about the touristic specialization of many rural regions. Such an orientation may however generate high opportunity costs, if it's not founded on an analysis of the competitive advantages, of the demand and supply and the market tendencies. The results also depend on the founding of a sustainable touristic development strategy, considering not only the economic aspects, but also environment, social and ethic aspects. This implies, first of all, a general strategy for development and a perfect corelation between all its components. Thus, an essential role is given to the partnership between the firms of the tourist channel, between these firms and firms of complementary fields and between public and private partners. The present study includes an analysis of the roles and formes of the public-private partnership in the sustainable development of the rural tourist destinations and it is organized in 4 parts. In the first part, I presented the particular aspects of the relationship tourism – development in the rural environment; the second part includes an application of the concept of quality integrated management in tourism, especially in the rural tourism. From the first two parts it results the necessity and the role of the public-private partnership in assuring the sustainability of the rural touristic destinations. The third part suggests some forms of the public-private partnership, with reference to the sustainable development principles. In the last part it is presented the importance of the rural tourism for Romania. The study closes up with suggestions for a strategy of sustainable tourist development of rural destinations.
Keywords: 330